Biospectroscopy reveals the effect of varying water quality on tadpole tissues of the common frog (Rana temporaria) - Strong, Rebecca J.; Halsall, Crispin J.; Ferenčík, Martin; Jones, Kevin C.; Shore, Richard F.; Martin, Francis L. (Elsevier Science, 2016)
Amphibians are undergoing large population declines in many regions around the world. As environmental pollution from both agricultural and urban sources has been implicated in such declines, there is a need for a biomonitoring approach to study potential impacts on this vulnerable class of organism. This study assessed the use of infrared (IR) spectroscopy as a tool to detect changes in several tissues (liver, muscle, kidney, heart and skin) of late-stage common frog (Rana temporaria) tadpoles collected from ponds with differing water quality. Small differences in spectral signatures were revealed between a rural agricultural pond and an urban pond receiving wastewater and landfill run-off; these were limited to the liver and heart, although large differences in body size were apparent, surprisingly with tadpoles from the urban site larger than those from the rural site. Large differences in liver spectra were found between tadpoles from the pesticide and nutrient impacted pond compared to the rural agricultural pond, particularly in regions associated with lipids. Liver mass and hepatosomatic indices were found to be significantly increased in tadpoles from the site impacted by pesticides and trace organic chemicals, suggestive of exposure to environmental contamination. Significant alterations were also found in muscle tissue between tadpoles from these two ponds in regions associated with glycogen, potentially indicative of a stress response. This study highlights the use of IR spectroscopy, a low-cost, rapid and reagent-free technique in the biomonitoring of a class of organisms susceptible to environmental degradation.
Biospektroskopie odhaluje vliv proměnné kvality vody na tkáně pulců skokana hnědého (Rana temporaria)
Keywords: amphibian declines; environmental pollution; IR spectroscopy; liver; tadpoles; úbytek obojživelníků; znečištění životního prostředí; IČ spektroskopie; játra; pulci